2000
DOI: 10.2307/369185
|View full text |Cite
|
Sign up to set email alerts
|

When Women Ask the Questions: Creating Women's Studies in America

Abstract: History of Education Quarterly need of 'normal' families, and even a potential responsibility of the state" (p. 5), we learn why that responsibility is still more potential than real.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Instead, structures specific to gender and feminist knowledge seem to matter more. The establishment of women's studies was a critical and hard-fought innovation in higher education that signified the valorizing of women's knowledge, research methods, and topics of study (Boxer, 2001). Since being offered in the late 1960s by only a handful of HEIs, most HEIs in the U.S. now offer at least a women's studies course, if not an undergraduate major or minor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, structures specific to gender and feminist knowledge seem to matter more. The establishment of women's studies was a critical and hard-fought innovation in higher education that signified the valorizing of women's knowledge, research methods, and topics of study (Boxer, 2001). Since being offered in the late 1960s by only a handful of HEIs, most HEIs in the U.S. now offer at least a women's studies course, if not an undergraduate major or minor.…”
Section: Discussionmentioning
confidence: 99%
“…Prior empirical work has found that women continue to face epistemic exclusion and scholarly devaluation in the academy, with consequences for promotion and tenure decisions (Settles et al, 2022). Women and gender studies programs legitimize and preserve feminist knowledge (Boxer, 2001). When institutionalized as departments, they provide new faculty lines through which more women may enter the institution (Scully, 1996).…”
Section: Transformations In Gender-and Diversity-supportive Structuresmentioning
confidence: 99%
“…11 7 In the US endeavors to introduce women's studies into universities began in the 1960s while the German women's movement made its way into academia somewhat later in the 1980s (Boxer 1998: 161;Hark 2005). For in-depth discussion of the German history of academic feminism see Hark (2005), for the US see Boxer (1998). 8…”
Section: Methodsmentioning
confidence: 99%